On the Decomposition of the Narcotic α-pyrrolidinovalerophenone in Nasway - L. I. Modinova; O. V. Panteleeva (Теория и практика судебной экспертизы, 2020)
The article provides information on the decomposition of the narcotic α-pyrrolidinovalerophenone (α-PVP) in nasway and the results of the study of the decomposition rate for the drug in an alkaline environment. It is shown that in a week, the content of α-PVP in nasway reduces by almost two times, and in 1,5–2 months, it is not found in the sample. Similar results were acquired for aqueous alkaline solutions of α-PVP.The information obtained can be useful for experts specializing in “research of narcotics, psychotropic substances and their precursors, potent and poisonous substances” when conducting examinations and research.